Water Management in UGM for Resilient and Healthy Campus - Panut Mulyono; Sentagi Sesotya Utami; Budi Prayitno; Fiki Rahmatika Salis; Faridah Faridah (Universitas Diponegoro, 2021)
Water management is one of the most challenging aspects of campus management. With a large number on campus population and limited water resources, water management is essential for achieving a resilient and healthy campus. In this paper, we explain two targets in UGM water management: water efficiency and water conservation. Both objectives are significantly related; however, each goal has a different approach to the method for the design approach and strategies in the implementations. Water efficiency is included in building new buildings and retrofitting the existing ones. Meanwhile, water conservation is implemented to calculate potential alternative water resources in UGM, including water treatment, to produce freshwater as an additional water supply. We also explain how water management is implemented in UGM from the highest Directorate to the lowest units. Through our method and best practices in UGM, we hope our paper could be a reference for other universities who want to implement a water management program.